Chemical constituents from the aerial parts of Achillea alpina and their chemotaxonomic significance. (April 2022) - Li, Xiuwei; Wu, Xia; Guo, Qiang; Liu, Changli; Yue, Hucheng; Tian, Jiayi; Liu, Zongyang; Xiao, Meng; Li, Ang; Ning, Zhongqi; Zan, Ke; Chen, Xiaoqing
Abstract: Phytochemical investigation of the aerial parts of Achillea alpina led to the isolation of sixteen compounds, including six sesquiterpenes (1 - 6 ), two polyacetylenic alcohols (7 - 8 ), three lignans (9 - 11 ), and five fatty acids (12 - 16 ). Their structures were identified by spectroscopic analysis of UV, IR, MS and NMR, and in comparison with the those reported data in the references. Among them, five compounds (10 - 14 ) were first obtained from the family Compositae, six compounds (1 - 3, 7, 15 and 16 ) were first reported from the genus Achillea, and three compounds (4, 5 and 8 ) were first obtained from this plant. The chemotaxonomic significance of constituents was also discussed. Highlights: Compounds 10 - 14 were first isoluted from the family Compositae, and compounds 1 -3, 7, 15 and 16 were first isoluted from the genus Achillea . Compounds 7 -8 can serve as biomarkers for the family Compositae. Compound 6 can be recognized as chemical fingerprints for the genus Achillea. Compound 5 suggested a close relationship between the genera Achillea and Artemisia. Compounds 1 -3 can be chemical fingerprints for A. alpina to distinguish A. alpina L. from the genus Achillea.